Understanding Exploitation in Consensual Sex Work to Inform Occupational Health & Safety Regulation - Benoit, Cecilia M. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The impetus behind this Special Issue emerged from a quest to move beyondbinary thinking in the contemporary period about people who sell sexual services,including recent disputes about "sex trafficking vs. prostitution" and"criminalization vs. decriminalization", to encourage theoretical and empiricalscholarship by exploring how sex work actually operates under different regulatoryregimes. The volume includes contributions from scholars of different socialsciences backgrounds based in five countries- New Zealand, the United Kingdom,Brazil, the United States and Canada. The article topics range widely,and both quantitative and qualitative research methods are showcased. The empiricalevidence presented adds to our current understanding of the complexityof this phenomenon of sex commerce/prostitution, which is found to be largelya problem of social inequality within and across capitalist societies. The authorscall for policies to address occupational and societal wide inequities faced by sexworkers across many countries.